Etymology and the Technique of Word Formation - Syeda Fasiha Abid; Tariq Mahmood (بازیافت, 2025)
<!--StartFragment--> <span style="font-size: 14.0pt; font-family: "Times New Roman",serif; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: "Times New Roman"; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi;" lang="EN-US">The word Ishtiqaq (derivation) is derived from the Arabic root Shaqq, which means to cut, tear, or separate. A related word in Arabic is Ishtiq, which means to take a half or obtain a part. In this context, Ishtiqaq refers to the process through which new words are formed by breaking or combining existing ones. The word that is formed or derived from a root is called mushtaq (derived word). Thus, it can be said that Ishtiqaq itself is derived from Shaqq, symbolizing the extraction or creation of new words from existing linguistic units. <!--EndFragment-->